Educational Service Pricing Strategies in the Perspective of Islamic Education Marketing Management - Amarullah, Mohammad Syarifuddin; Farisi, Ahmad Nu'man; Zohriah, Anis; Djabidi, Faizal (PT FORMOSA CENDEKIA GLOBAL, 2025)
Determining the price of educational services is one of the strategic elements in education marketing management, especially in Islamic educational institutions that have a dual mission: to produce people with Islamic character while ensuring the sustainability of the institution. This article explores the fundamentals of education service pricing strategies, pricing strategy objectives, and relevant techniques. With a descriptive-qualitative approach, this study aims to provide practical and academic insights for managers of Islamic educational institutions in managing the price aspect as a strategic marketing instrument.